Analisis Klausa Verbal Transitif Artikel Populer Karya Muh. Syahrul Padli pada Media Masa Medium Edisi April 2024 - Iin Iduljanah; Alifia Shifa Latif; Aurel Theresiana Bangun; Laela Nabila; Arinas Sa’dah; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Muhammad Noor Ahsin (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
In this research the author took a study in the field of syntax. The syntactic survey in this research focuses on the types of transitive verb clauses in popular articles by Muh. Syahrul Padli in the April 2024 edition of the medium. This research aims to classify and analyze transitive verb clauses. This research is conducted with a synchronic approach that seeks to describe and provide the types and structures of clauses presented descriptively and qualitatively. The purpose of this study is to provide insight into the classification of verb clauses and provide examples of their classification in the description text in “Popular Articles by Muh. Syahrul Padli on Medium Masa Media April 2024 Edition”. Data collection in this research uses note-taking and listening/reading techniques. Data analysis techniques include data reduction, analysis, interpretation, and triangulation after which a conclusion is drawn. The data presentation technique is informal data presentation. From the data analysis, it can be concluded that some form of verb clauses in description texts, namely: transitive verb clauses. This article can be useful for students because it gives insight into the structured division of verb clauses and also the use of verb clauses in the article.